PARTISIPASI PEMILIH DISABILITAS PADA PEMILIHAN UMUM TAHUN 2019 (STUDI KOMPARASI DI KECAMATAN WANGON DAN RAWALO KABUPATEN BANYUMAS) - Kharismaningtias, Indah Dwi -; Sardini, Nur Hidayat -; Astuti, puji - (Journal of Politic and Government Studies, 2024)
The low level of participation of disability groups is an issue that needs attention considering that disabled voters are an inseparable segment of the election. The phenomenon of participation gaps that occurred in Wangon and Rawalo Districts, Banyumas Regency in the 2019 election became the starting point for the departure of research that needs to be carried out. Rawalo sub-district as the area with the lowest participation of disabled voters only reached a participation rate of 20.37%, while Wangon sub-district as the region with the highest participation managed to contribute 82.24% participation. This study was conducted to compare the reasons why voters with disabilities in both regions participated or did not participate in the election along with the factors that influenced the high and low participation. Qualitative methods with descriptive-comparative research types are used to explore phenomena more deeply through data collection techniques in the form of interviews and documentation studies. The results of this study show that the high and low turnout in Wangon and Rawalo sub-districts is influenced by internal factors coming from the voter and external factors coming from the election organizer and the surrounding environment. Some of the problems that hinder disability involvement include suboptimal socialization intensity, lack of provision of electoral facilities and infrastructure, and lack of support and assistance from family. The factors that make it easier for people with disabilities to participate include the location of polling stations that are easy to reach and the provision of ball pick-up services on polling day. From this study, it was also found that aspects of political awareness and mentoring were the factors that most influenced the difference in participation rates in the two regions